An Analysis of Challenges Encountered by High School Delegates in International Conference - Prapassel, Luxvhyona Fharadhylla; Abrar, Mukhlash; Capah, Catherine Rohmoia; Sukarno, Berliana Sukma Tri (Universitas Pahlawan Tuanku Tambusai, 2025)
This research aimed to explore high school students’ challenges in an international conference. The research employed a qualitative method with a case study approach. The participants in this research were four high school students who had presented in one international conference. The researcher used purposive sampling to select the appropriate participants based on the criteria. To obtain data, the researcher interviewed the participants. In analyzing the data, the researcher used thematic analysis. The results of this research indicated that high school students experienced some challenges when presenting their paper in an international conference that was held in Malaysia, which were divided into three themes: language barriers (lack of vocabulary, grammar, and pronunciation), psychological issues (lack of confidence and anxiety), and performance (lack of preparation). Despite the comprehensive exploration of the topic, this study has some limitations. Firstly, the research solely focused on the experiences of high school students at international conferences. Future studies could explore their experiences in national forums for comparison. Secondly, the study included a relatively small sample size of only four participants. Including more participants in future research could lead to a more nuanced understanding of the challenges faced.